CORPORATE GOVERNANCE IMPLICATIONS ON THE BANK MANAGEMENT IN THE REPUBLIC OF MOLDOVA - Stela CIOBU; Ion CARA (Economica, 2020)
The topic of the article is of major importance for Moldovan banks as even some progress has been made in corporate governance in banks in recent years, its organization is still insufficiently developed. The article addresses the topic of corporate governance as an element of administration in banks in the Republic of Moldova, explaining the particularities of its use in banks. As a result of the research, it was identified that the quality of corporate governance has a significant importance on the efficiency of administration and the performance of banks in the Republic of Moldova. In order to achieve the objectives of the study, a wide information support is analysed, including: reports and publications of the NBM, other banks, international financial institutions, normative acts, etc. The applied research methodology is mainly based on secondary data, using quantitative analysis based on the use of scientific research methods, including synthesis method, comparative analysis, observation method, induction and deduction.